الصكوك الاسلامية كبدائل لتمويل العجز الموازني في الجزائر على ضوء التجربة الماليزية . - بارك نعيمة; بوشناف فايزة; بن داودية وهيبة (My University, 2021)
ملخص: تهدف هذه الدراسة إلى إبراز دور الصكوك الاسلامية في مواجهة أزمة العجز الموازني في الجزائر ودعم التنويع الاقتصادي للبلاد، وذلك من خلال استعراض التجربة الماليزية باعتبارها الرائدة في مجال التمويل بإصدار الصكوك الإسلامية وانعكاسات استخدام هذه الاداة في تمويل العجز الموازني للوقوف على الدروس المستفادة ، وذلك باستخدام المنهج التحليلي و المنهج الوصفي من خلال تحليل مؤشرات عجز الموازنة العامة للجزائر واستقراء اسبابه ونتائجه مبرزين نقاط ضعف التمويل غير التقليدي المنتهج منذ 2017 لعلاج العجز الذي تعاني منه الموازنة العامة للدولة ، و ما مدى إمكانات الصيغ التمويلية الاسلامية التي اقرتها وزارة المالية و بالأخص الصكوك الإسلامية في تمويل هذا العجز . الكلمات المفتاحية: التمويل غير التقليدي، الإصلاحات الاقتصادية الهيكلية، قانون النقد والقرض، الصكوك الإسلامية. Abstract: This study aims to highlight the role of Islamic instruments in facing the budget deficit crisis in Algeria and supporting the country's economic diversification, by reviewing the Malaysian experience as a pioneer in the field of financing by issuing Islamic instruments and the implications of using this tool in financing The budget deficit. To find out the lessons learned, using the analytical approach and the descriptive approach by analyzing the indicators of the general budget deficit of Algeria and extrapolating its causes and results, highlighting the weakness of the unconventional financing adopted since 2017 to treat the deficit in the state's general budget , And what are the capabilities of the Islamic financing formulas approved by the Ministry of Finance, especially Islamic instruments in financing this deficit. .